'A fragment of the explanation': the use and abuse of words. Issue 2 (1st December 2001) - Heath, Iona
Abstract : This paper explores the normative basis of power in language, story, labels and evidence, and attempts to show how these dimensions of power are used systematically to simplify the reality of exprience, deny ignorance and exclude uncertainty. Through the resulting abuse of words, doctors may often constrain and limit their patients' stories, consigning many of them to stories of failure, and reducing their capacity to celebrate, or even recognise, achievement.